Power Dynamics in Accounting-Related Strategic Decision-Making within Hospital Management: A Narrative Literature Review - Nurkholis Nurkholis; Endang Mardiati; Nurul Fachriyah; Made Aristia Prayudi (Fakultas Ekonomi Universitas Negeri Manado, 2024)
This paper aims to explore how power dynamics shape strategic decisions and performance measurement systems in hospital management, elucidating their impact on managerial choices in healthcare settings. Key themes and factors related to power dynamics in hospitals are identified, including the distribution of power among management teams, the influence of individual and group power dynamics, and the effects of power on decision-making across organizational levels. By synthesizing insights from previous research, this paper informs the development of theoretical frameworks and methodological approaches for studying the interplay between power dynamics and strategic decision-making in hospital management. Furthermore, it offers practical implications for hospital administrators and managers, providing guidance on navigating power dynamics to enhance decision-making effectiveness and organizational performance. This paper contributes to advancing our understanding of the complex dynamics of power and decision-making in hospital management, offering valuable insights for both research and practice in healthcare administration.